TALKING ABOUT END OF LIFE: MARKETING ADVANCE CARE PLANNING TO RESIDENTIAL AGED CARE FACILITIES. Issue 2 (1st June 2013) - Piercy, J; Walker, H; Prior, T; Buchanan, G; Greeve, Kim
Abstract : Background: Of the 143 932 Australians who die each year, 10% die in residential aged care facilities (RACFs). 25% of these deaths occur within 6 months of admission. Frequently residents are transferred to hospital at the end of life. Aim: To assist RACF staff to identify residents with irreversible deteriorating conditions. facilitate case conferences to record resident's and family's wishes record advanced care plans (ACPs) respond to and enact ACPs. Methods: The Talking about end of life programme was branded and marketed to RACFs resulting in an inundation of registrants. To translate theory to practice, training was delivered to link teams from each RACF. Tailored mentoring encouraged ACP, team building, ongoing education and death reviews. Pre and post intervention surveys revealed ACP practices. Results: Project results include increased numbers of ACPs and less residents transferred to hospital to die. Enablers and barriers to success were identified. Where ACPs were developed, staff experienced increased satisfaction in caring for residents in the terminal phase. Discussion: The need and desire for training in ACP and care of the dying within RACFs was evident by the overwhelming response. Willingness of general practitioners to discuss end of life issues was pivotal to success. Risks included sustaining the trained workforce and supportive systems. Direct benefits of ACP to residents and families needs further exploration. Conclusion: The programme's marketing strategy was successful. Training alone is not enough, a systems approach to modifying and improving practice is essential to ACPs becoming routine practice in RACFs.